Grape seed proanthocyanidin extract targets p66Shc to regulate mitochondrial biogenesis and dynamics in diabetic kidney disease - Song, Yiyun; Yu, Hui; Sun, Qiaoling; Pei, Fei; Xia, Qing; Gao, Zhaoli; Li, Xianhua (Frontiers in Pharmacology, 2023)
Background. Mitochondrial biogenesis and dynamics are associated with renal mitochondrial dysfunction and the pathophysiological development of diabetic kidney disease (DKD). Decreased p66Shc expression prevents DKD progression by significantly regulating mitochondrial function. Grape seed proanthocyanidin extract (GSPE) is a potential therapeutic medicine for multiple kinds of diseases. The effect of GSPE on the mitochondrial function and p66Shc in DKD has not been elucidated. Hence, we decided to identify p66Shc as a therapeutic target candidate to probe whether GSPE has a renal protective effect in DKD and explored the underlying mechanisms. Methods. In vivo, rats were intraperitoneally injected with streptozotocin (STZ) and treated with GSPE. Biochemical changes, mitochondrial morphology, the ultrastructure of nephrons, and protein expression of mitochondrial biogenesis (SIRT1, PGC-1α, NRF1, TFAM) and dynamics (DRP1, MFN1) were determined. In vitro, HK-2 cells were transfected with p66Shc and treated with GSPE to evaluate changes in cell apoptosis, reactive oxygen species (ROS), mitochondrial quality, the protein expression. Results. In vivo, GSPE significantly improved the renal function of rats, with less proteinuria and a lower apoptosis rate in the injured renal tissue. Besides, GSPE treatment increased SIRT1, PGC-1α, NRF1, TFAM, and MFN1 expression, decreased p66Shc and DRP1 expression. In vitro, overexpression of p66Shc decreased the resistance of HK-2 cells to high glucose toxicity, as shown by increased apoptosis and ROS production, decreased mitochondrial quality and mitochondrial biogenesis, and disturbed mitochondrial dynamic homeostasis, ultimately leading to mitochondrial dysfunction. While GSPE treatment reduced p66Shc expression and reversed these changes. Conclusions. GSPE can maintain the balance between mitochondrial biogenesis and dynamics by negatively regulating p66Shc expression.